Development of Flexible Nanocomposites Based on Poly(ε-caprolactone) for Tissue Engineering Application: The Contributing Role of Poly(glycerol succinic acid) and Polypyrrole. (5th February 2022) - Jafari, Aliakbar; Fakhri, Vafa; Kamrani, Soosan; Reza Ghaffarian Anbaran, S.; Su, Chia-Hung; Goodarzi, Vahabodin; Pirouzfar, Vahid; Ali Khonakdar, Hossein
Graphical abstract: Highlights: PGSu improved the mechanical properties and hydrophilicity of the PCL matrix. Conductivity and antibacterial properties were obtained for PPy-coated scaffolds. Surface wettability was enhanced by incorporating n-HA and in-situ PPy coating. The biodegradation rate could be adjusted by changing the composition of samples. In-vitro cell viability improved noticeably for PPy-coated scaffolds. Abstract: Poly(ε-caprolactone) (PCL), a semi-crystalline polyester, has been widely used for tissue engineering and regenerative medicine applications due to its favorable mechanical properties, biocompatibility, and long-term biodegradation. Despite desirable physical and chemical characteristics, PCL shows low hydrophilicity, thus constraining its utility for biomedical applications. Here, we report the synthesis and characterization of elastomeric PCL/poly(glycerol succinate) (PGSu) blends and their nanocomposites with improved surface wettability and tunable mechanical properties, and controlled biodegradation. Also, the effect of the polypyrrole (PPy) coating layer on the properties of scaffolds was investigated. By tailoring the surface and bulk properties of scaffolds using a change in PCL to PGSu ratio, adding nano-hydroxyapatite (n-HA) as a filler, and deposition of PPy on the scaffolds, it is possible to engineer scaffolds with customized degradation and mechanical properties. The addition of PGSu and n-HA increased hydrophilicity of the PCL matrix, developed its mechanical performance, and enhanced in-vitro cell metabolic activity. It was shown that Young's modulus of PCL-PGSu-based scaffolds could be tuned from about 11.5 MPa to 4.5 MPa by altering the amount of PGSu and n-HA within the PCL network. The crystallinity of PCL was also considerably influenced by PGSu and n-HA. Moreover, deposition of PPy on the scaffolds resulted in a desirable antibacterial activity and electrical conductivity of about 5*10 -2 S/cm. As expected, the rate of degradation increased with an increase in PGSu concentration. At the same time, the PPy coating layer delayed the degradation process, indicating that the biodegradation rate of the PCL matrix can be regulated. PCL-PGSu-based scaffolds also supported cell viability and proliferation, where PPy coating significantly improved cell viability. Therefore, the synthesized scaffolds can be used for a range of tissue engineering applications.